INNOVATION AS AN ENGINE OF ECONOMIC GROWTH IN PERU - Quijandría, Benjamin (2024)
Innovation, fundamental in various fields, entails the sustained creation and adoption of new ideas, products, or processes. Recognized by the Organization for Economic Cooperation and Development (OECD) as a driver of growth and fueled by it. The article analyzes the innovation generation process, various interpretations or scopes, as well as its evolution over time, having transitioned from closed innovation to open innovation, a factor that significantly boosted its contribution to society. A key aspect is its relationship with economic growth, highlighting the need to foster innovation in the Peruvian context.